Investİgatİon of Conservatory and Music Education Department Students' Opinions on Turkish Music Composition (Tokat Province Example) - Baş, Ahmet Hakan; Karaca, Tolga (Fırat University, 2025)
This research, which aims to investigate the opinions of Tokat Gaziosmanpaşa University State Conservatory and Music Education Department students on Turkish music composition, aims to reveal the students' opinions on this subject and to make suggestions on the subject. In this context, a student information and opinion form was prepared by taking expert opinions. This form was applied to students studying in the spring semester of the 2022-2023 academic year and the data collected was analyzed to reach the research results. Qualitative descriptive scanning model was used in the research. The data obtained after the form was analyzed using the content analysis method. These data of student statements, analyzed by the researchers and grouped within the scope of the research questions, were compiled into a report with citations. According to the research results; It was revealed that the most well-known composer among the students was Tanburi Cemil Bey, and the most listened to form was the song form. Additionally, it was determined that 80% of the students participating in the research had no experience with composition. It is thought that the findings obtained from the research will be important in terms of giving ideas to institutions aiming to open composition departments in institutions that provide Turkish music education. In future research on Turkish music composition, it is recommended to work with different student groups.

Tokat Gaziosmanpaşa Üniversitesi Devlet Konservatuvarı ve Müzik Eğitimi Anabilim Dalı öğrencilerinin Türk müziği besteciliğine ilişkin görüşlerinin araştırılmasına yönelik olan bu araştırmada, öğrencilerin bu konu hakkındaki görüşlerini ortaya çıkarmak, konuya yönelik öneriler getirmek amaçlanmıştır. Bu kapsamda uzman görüşleri alınarak öğrenci bilgi ve görüş formu hazırlanmıştır. 2022-2023 eğitim-öğretim yılı bahar döneminde eğitim gören öğrencilere bu form uygulanmış ve toplanan veriler analiz edilerek araştırma sonuçlarına ulaşılmıştır. Araştırmada nitel betimsel tarama modeli kullanılmıştır. Form sonrasında elde edilen veriler, içerik analizi yöntemi ile analiz edilmiştir. Araştırmacılar tarafından analiz edilen, araştırma soruları kapsamında gruplandırılan öğrenci ifadelerine ait bu veriler, atıflarla birlikte rapor haline getirilmiştir. Araştırma sonuçlarına göre; öğrenciler arasında en çok bilinen bestekârın Tanburi Cemil Bey, en çok dinlenen formun şarkı formu olduğu ortaya çıkmıştır. Ayrıca, araştırmaya katılan öğrencilerin %80’inin bestecilik ile ilgili tecrübelerinin olmadığı tespit edilmiştir. Araştırmadan elde edilen bulguların, Türk müziği eğitimi veren kurumlarda bestecilik bölümleri açmayı hedefleyen kurumlara fikir vermesi bakımından önemli olacağı düşünülmektedir. Türk müziği besteciliği ile ilgili gelecekte yapılması düşünülen araştırmalarda, farklı öğrenci grupları ile çalışma yapılması önerilmektedir.
Konservatuvar ve Müzik Eğitimi Anabilim Dalı Öğrencilerinin Türk Müziği Besteciliğine İlişkin Görüşlerinin Araştırılması (Tokat İli Örneği)
Keywords: Specialist Studies in Education (Other); Eğitim Üzerine Çalışmalar (Diğer)